SITEPIS Contraception is an Extension Officer in Providing Information on Family Planning in Indonesia - Hariyanti, Hariyanti; Khatimah, Husnul; Kristianto, Jusuf; Gumilang, Intan; Hamidiyanti, Baiq Yuni Fitri (JURNAL INFO KESEHATAN, 2023)
This study addresses the vital role of information as a reproductive health right and emphasizes the responsibility of family planning officers, including health workers, to disseminate accurate information for ensuring public reproductive health. The research focuses on evaluating the effectiveness of SITEPIS Contraception, an online information service designed to aid family planning officers in conveying contraceptive information. SITEPIS is a web application offering comprehensive information on contraception, medical eligibility criteria, and a live chat service. This study involves 28 family planning officers at sub-district and village levels in Bogor and West Lombok districts. Employing a descriptive research approach, the study includes socialization events introducing Sitepis Contraception, encouraging usage, and collecting officers' evaluations. Results indicate positive feedback from all officers, citing the website's appealing design, user-friendly accessibility, and essential features for effective information delivery. Despite challenges related to internet network support in certain areas, officers express willingness to use the SITEPIS website for their community information duties. Notably, while face-to-face interaction is preferred by most officers, SITEPIS contraception serves as a valuable tool for information dissemination. The study underscores the underutilization of online information as the primary method among family planning officers in Indonesia. Despite this, it recognizes the potential of online platforms, like SITEPIS, in reaching diverse societal levels. The findings emphasize the need for further examination of SITEPIS Contraception from the community's perspective, the primary target audience, to enhance its effectiveness. In conclusion, the study advocates for the integration of online information tools to empower family planning officers in fulfilling their crucial role as information providers.